Michigan vs. the boys - Allen, Carrie, 1976- (2019)
"After her girls' ice hockey team is cut for budget reasons, Michigan tries out for the boys' team, and earns a place on the starting lineup. But when she bests her teammates with her skills and her refusal to back down, hazing crosses the line into assault."--
Keywords: Women athletes -- Juvenile fiction; Hockey players -- Juvenile fiction; Hazing -- Juvenile fiction; Bullying -- Juvenile fiction; Sex discrimination -- Juvenile fiction; Young adult fiction; Bildungsromans